Association of acepromazine with propofol in giant amazon turtles Podocnemis expansa reared in captivity - Ferreira Alves-Junior, Jose Roberto; Scarpa Bosso, Andrea Cristina; Andrade, Mariana Batista; Jayme, Valeria de Sa; Werther, Karin [UNESP]; Quagliatto Santos, Andre Luiz (Acta Cirúrgica Brasileira, 2012)
PURPOSE: To evaluate the effects of different concentrations of an anesthetic association in giant amazon turtles (Podocnemis expansa).METHODS: Twenty healthy P. expansa of both sexes weighing between 1.0 and 1.5kg commercially bred in the Araguaia River Valley, Goias, Brazil, were separated into two groups (G1 n=10 and G2 n=10). Each group received a respective protocol: P1=acepromazine (0.5 mg/kg IM) and propofol (5 mg/kg IV) and P2=acepromazine (0.5 mg/kg IM) and propofol (10 mg/kg IV). The acepromazine was administered in the left thoracic member and the propofol in the cervical vertebral sinus. Assessments were made of the anesthetic parameters of locomotion, muscle relaxation, response to pain stimuli in the right thoracic and pelvic members and heartbeat.RESULTS: The anesthetic induction time was the same for both protocols (P1 and P2); however the P2 effects were of a longer duration.CONCLUSION: The sedation achieved with both protocols (P1 and P2) were satisfactory for the biological sample collection, physical examinations and minor surgeries on this species.

OBJETIVO: Avaliar os efeitos de uma associação anestésica com diferentes concentrações em tartarugas-da-amazônia (Podocnemis expansa). MÉTODOS: Vinte P. expansa, hígidas, de ambos os sexos, com massa corporal entre 1,0 e 1,5 kg, de um criatório comercial localizado no vale do rio Araguaia, Goiás, Brasil, foram distribuídas em dois grupos (G1 n=10 e G2 n=10). Cada grupo recebeu um protocolo sendo: P1 = acepromazina (0,5 mg/kg IM) e propofol (5 mg/kg IV) e P2 = acepromazina (0,5 mg/kg IM) e propofol (10 mg/kg IV), aplicados nos grupos G1 e G2, respectivamente. A acepromazina foi aplicada no membro torácico esquerdo e o propofol no seio vertebral cervical. Foram avaliados os parâmetros anestésicos: locomoção, relaxamento muscular, resposta aos estímulos dolorosos no membro torácico direito e nos membros pelvinos e frequência cardíaca. RESULTADOS: O tempo de indução anestésica foi o mesmo para ambos os protocolos (P1 e P2), porém o P2 apresentou efeitos mais duradouros. CONCLUSÃO: As sedações obtidas por esses protocolos (P1 e P2) foram satisfatórias para a colheita de amostras biológicas, exames físicos e realização de pequenos procedimentos cirúrgicos nesta espécie.
Associação da acepromazina com propofol em tartarugas-da-amazônia Podocnemis expansa criadas em cativeiro
Keywords: Anesthesia; Acepromazine; propofol; Reptiles; Turtles